FAKTOR RISIKO KANKER PARU DI KOTA SEMARANG - -, Sutaryono - (MOTORIK Jurnal Ilmu Kesehatan (Journal of Health Science), 2011)
Background : Lung cancer is one of  the non communicable disease the health problem in developed countries and also in developing countries. It is an uncontrollable tumour of lung cells, either from the bronchus mucus, bronchioles, alveolus or other parts of the lungs. Same of the risk factors of lung cancer are carsinogenic, diet, demography and genetic. Methode : This research is an analytical research with a case-control design. The subject in this study were lung cancer patients at Dr. Kariadi hospital Semarang between January 2008 and Marc 2009 for the case group. The number of subject who could eventually be included as case samples in this study was 47 patients for the case group and  47 patients for the control group. The primary variable of interest were lung lung cancer of sex, age, smoking, passive smoking, occupational exposures, vehicle smoke exposures, insect burning exposures, low consumption of fruit and vegetable, and family history. Results : The statistic analysis indicated at sex  increase risk 0,664 (95%, CI : 0,273-1,619), Age increase risk 4,133 (95% CI : 1,421-12,025), smoking 7,632 (95% CI : 2,028-28,724), passive smoking 6,571 (95% CI : 2,070-20,858), occupational exposures 0,427(95%, CI : 0,145-1,255), vehicle smoke exposures 0,597 (95%, CI:0,264-1,352), insect burning exposures 1,723  (95%, CI : 0,743-3,994, p : 0,203), low consumption of fruit and vegetable 4,670 (95% CI : 1,589-13,726), and family history  2,044 (95%, CI : 0,179-23,348). Conclusion : The findings from this research a strong relationship was observed between lung cancer of age p : 0,009 (p<0,05), smoking  p : 0,003, passive smoking p : 0,001 and low consumption of fruit and vegetable p = 0,005. Keywords : Lung cancer, smoking, exposures, diet, family history